Literasi Digital sebagai Tameng Misinformasi: Strategi Pendidikan di Era Media Sosial - Shofi, Ajmal Ramzani Nasywa (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has significantly changed the way students access, understand, and use information in the learning process. Generation Z and Alpha, as a generation that grew up with the internet, are more likely to use social media such as TikTok, YouTube, and Instagram as their primary source of learning compared to textbooks. This change presents both opportunities and challenges. On the one hand, social media can increase learning motivation, provide engaging visual-audio experiences, and facilitate interactive learning. However, on the other hand, the phenomenon of information flooding poses a risk in the form of exposure to hoaxes, misinformation, and superficial understanding due to the dominance of short content without in-depth explanation. Teachers as learning facilitators are required to adapt to this new learning pattern. The role of teachers is no longer just a conveyor of knowledge, but also a director of digital literacy who is able to guide students in sorting, evaluating, and utilizing information critically. Strategies that can be carried out include integrating digital literacy into the curriculum, teaching information verification skills, and using social media as an entrance to deeper learning. The challenges faced in Indonesia include limited internet access, the availability of devices, and the lack of teacher training, so a more comprehensive policy is needed for the equitable distribution of digital literacy. This article emphasizes the importance of collaboration between teachers, schools, and policymakers in optimizing the use of digital media.